Asian American studies now : a critical reader - Wu, Jean Yu-wen Shen, 1948-; Chen, Thomas C., 1982-; Lee, Robert G., 1947-; Okihiro, Gary Y., 1945-2024; Zia, Helen; Eng, David L., 1967-; Han, Shinhee, 1963-; Kim, Elaine H.; McGregor, Davianna; Omi, Michael; Winant, Howard; Lee, Erika; et al. (Rutgers University Press, 2010)
Asian American Studies Now represents the changes occurring in Asian American communities and the world that require a reconsideration of how the interdisciplinary field of Asian American studies is defined and taught. The editors have selected essays for the significance of their contribution and their clarity, brevity, and accessibility to readers with little to no prior knowledge of Asian American studies, and feature reprints of seminal articles and groundbreaking texts, as well as bold new scholarship.